2011
DOI: 10.1097/ajp.0b013e318208c8a2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Pain Self-efficacy

Abstract: Further research should focus on assessing responsiveness and interpretability of these questionnaires. Researchers should select questionnaires that are most appropriate for their study aims and population and contribute to further validation of these scales. Future research should measure outcome expectancy alongside self-efficacy to best predict future behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
99
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 55 publications
1
99
0
3
Order By: Relevance
“…38 The CPSS has proven valid with significant associations with measures of mood, depression, feelings of hopelessness, and pain. 39 In our study sample of hospitalized patients, we used the CPSS-PM and CPSS-CS and Cronbach's alpha for the two subscales were 0.88 and 0.92, respectively.…”
Section: Patient Self-efficacymentioning
confidence: 99%
“…38 The CPSS has proven valid with significant associations with measures of mood, depression, feelings of hopelessness, and pain. 39 In our study sample of hospitalized patients, we used the CPSS-PM and CPSS-CS and Cronbach's alpha for the two subscales were 0.88 and 0.92, respectively.…”
Section: Patient Self-efficacymentioning
confidence: 99%
“…Previous research has shown the Pain Self-Efficacy Questionnaire to be a reliable and valid measure of pain self-efficacy in patients with musculoskeletal pain. 36,39 One-Year Follow-up Interview A telephone interview was used to determine participants' return-to-work status and levels of pain intensity 1 year following treatment onset. Return-to-work status (yes/no) was determined by whether participants were working full-time at the time of the interview.…”
Section: Methodsmentioning
confidence: 99%
“…Even though frequently used in WAD-studies and found reliable, the SES does not seem to be validated in this context (168). Also some of the questions might be less relevant for some people, like for instance working on a house repair, raking leaves and shoveling snow.…”
Section: Outcome Measurementsmentioning
confidence: 99%